A mechanistic analysis of delamination of elastic coatings from the surface of plastically deformed stents. (1st August 2021) - Máirtín, É.Ó; Concannon, J.; Parry, G.; McGarry, J.P.
Abstract: Several medical papers have reported delamination of the coating from the stent-substrate following intravascular deployment leading to adverse outcomes for patients. However, the mechanisms of delamination of such polymer coatings from the surface of a stent due to large deformations during device deployment have not been studied. In this paper, a novel and in-depth investigation of the mechanisms and parameters that govern stent-coating delamination is performed, using a cohesive zone formulation to simulate the evolution of traction at the stent-coating interface. The study firstly analyses the behaviour of elastic coatings on idealised elastic stent substrates. Simulations reveal that the mode mixity of delamination is strongly dependent on the level of stent deployment at initiation. In general, peak normal tractions exceed peak shear tractions at low levels of stent deployment whereas the reverse trend is computed at high levels of stent deployment. Interface tractions increase with both increasing stent thickness and coating thickness suggesting that thinner stents and thinner coatings should be utilised for the delivery of antiproliferative drugs to reduce the risk of coating delamination. Next, the influence of stent plasticity on interface tractions and coating delamination is investigated. Even at low levels of deployment, plastic yielding occurs in the stent hinge region and the patterns of normal and shear tractions are found to be significantly more complex than those computed for the elastic stents, with both tensile and compressive regions of normal traction occurring in the stent arch. At a high level of stent deployment shear tractions at the stent-coating interface are computed to increase with decreasing strain hardening modulus. The findings of this paper provide a new insight into the stress-state at the stent-coating interface as a function of the stent design parameters and large deformation elasticity and plasticity during deployment, allowing for a more reliable assessment of the limits relating to safe implantation of coated stents.